Evaluation and modelling of customer experience in online retail banking in India and its significance for enhancing customer loyalty - Kumar, Puneet (2021)
Online banking had been an ongoing opportunity of strong growth for retail banks. In developing countries like India, online banking has been seen only as an alternative banking channel until today. Numerous researches had been examining online banking behaviours across the world. However, there is still an existing void addressing the context of countries and banking segments independently. The behaviour of each country's online banking users may deviate due to different culture, beliefs, technological infrastructure, and income level they perceive. Thus, it is inevitable to study the behavioural aspect of online banking users independently.